2009
DOI: 10.1080/01490450903263400
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology of Fe (hydr)oxide Mats and Basaltic Rock from Vailulu'u Seamount, American Samoa

Abstract: Microbial community analysis of a deep-sea volcanic and hydrothermal system at Vailulu'u Seamount yielded 89 new organisms and three detailed 16S-rRNA gene clone libraries (one rock and two microbial mats). Proteobacterial communities dominate in most environments, but important differences are found between microbial mats from distinctly different geochemical environments and for the rock surface. Many cultured organisms are metabolically and functionally diverse, displaying at least two of the tested functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 62 publications
(105 reference statements)
3
62
0
1
Order By: Relevance
“…These are the first deep-sequencing results for seafloor basalts. Previous studies have illustrated that basalts are host to diverse and abundant microbial communities dominated by bacteria (2,4,27,(61)(62)(63)(64). Pyrotag sequencing of the V6 hypervariable region of 16S rRNA supports earlier findings that Gammaproteobacteria are the most abundant bacterial class on seafloor basalts and that the Chromatiales and Thiotrichales orders of sulfur-oxidizing bacteria are among the basalt-associated Gammaproteobacteria (2,4,62).…”
supporting
confidence: 72%
“…These are the first deep-sequencing results for seafloor basalts. Previous studies have illustrated that basalts are host to diverse and abundant microbial communities dominated by bacteria (2,4,27,(61)(62)(63)(64). Pyrotag sequencing of the V6 hypervariable region of 16S rRNA supports earlier findings that Gammaproteobacteria are the most abundant bacterial class on seafloor basalts and that the Chromatiales and Thiotrichales orders of sulfur-oxidizing bacteria are among the basalt-associated Gammaproteobacteria (2,4,62).…”
supporting
confidence: 72%
“…5D) (479). Additional studies have confirmed colonization of fresh mineral surfaces by microorganisms (133,425,517,540). Further support for microbial activity in crustal materials derives from the observation of conspicuous "tubes" that are observed in basalt glasses, which are hypothesized to be generated by microorganisms growing into the surfaces of minerals (162,163,178,179,188).…”
mentioning
confidence: 93%
“…This has resulted in the isolation of novel, autotrophic Fe-oxidizing Gammaproteobacteria (134) and diverse Mn-oxidizing bacteria (541). The isolated Mn-oxidizing bacteria were all Alpha-or Gammaproteobacteria, as were most of the Mn-oxidizing isolates grown from a Vailulu'u Seamount basalt (517). Interestingly, many of the isolates from the Vailulu'u Seamount were capable of both Fe and Mn oxidation.…”
Section: Cultivated Prokaryotes From the Dark Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…These were psychrophilic facultative anaerobes that were related to alphaproteobacteria and gammaproteobacteria. More recently, Sudek et al (2009) reported that heterotrophic Pseudomonas/Pseudoalteromonas-like gammaproteobacteria isolated from a volcanic seamount could also catalyse ferrous iron oxidation under micro-aerobic conditions, and therefore contribute to the formation of iron mats in the deep oceans.…”
Section: Neutrophilic Aerobic Iron-oxidizing Proteobacteriamentioning
confidence: 99%